Early activity patterns and thalamocortical synaptic plasticity during the 'brain spurt' period - A.R. Nasretdinov; R.N. Khazipov (Учёные записки Казанского университета: Серия Естественные науки)
Development of thalamocortical sensory maps during the “brain spurt” period, which spans through the second half of gestation in human and neonatal period in rodents, is characterized by particular immature patterns, which are thought to be implicated in the activity-dependent formation of the topographic thalamocortical circuits. Here, we discuss how these early activity patterns can support plasticity at the developing thalamocortical synapses and contribute to the refinement of the initially crude protomaps through the competition between sensory inputs for the cortical territories.